2021
DOI: 10.3390/ijerph18041841
|View full text |Cite
|
Sign up to set email alerts
|

The Dramatic Consequences of an Accidental Ligation of the Celiac Trunk during Surgery Performed on a Child with Neuroblastoma

Abstract: Neuroblastoma is the most common extra-cranial solid tumor in infants and young children, and accounts for approximately 8–10% of all childhood cancers. The International Neuroblastoma Staging System (INRGSS) is based on the age of patient and preoperative imaging, with attention paid to whether the primary tumor is affected by one or more of specific Image-Defined Risk Factors (IDRFs). Patients are classified into the following groups: locoregional L1 and L2 (absent or present IDRFs respectively), M stage (a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…However, a few studies reported delayed necrosis as a complication. A case was reported in which the celiac artery was accidentally ligated during pediatric surgery, and stomach necrosis developed on post-operative day (POD) 59 [ 6 ]. In another case, liver failure was noted 6 days after abdominal trauma with CAI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies reported delayed necrosis as a complication. A case was reported in which the celiac artery was accidentally ligated during pediatric surgery, and stomach necrosis developed on post-operative day (POD) 59 [ 6 ]. In another case, liver failure was noted 6 days after abdominal trauma with CAI [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Necrosis probably developed gradually as the blood flow decreased slowly. In a pediatric case, necrosis occurred on POD 59 [ 6 ], which is long after the ligation of the celiac artery, indicating that blood flow was maintained to some extent even after the ligation of the celiac artery. In the current case, the root of the celiac artery was not ligated; however, the branch arteries were ligated; therefore, it is comparable with a case of CAI.…”
Section: Discussionmentioning
confidence: 99%